Improved health status of severe COPD patients after being included in an integrated primary care service: A prospective cohort study. Issue 1 (31st December 2022) - de Jong, Corina; van Boven, Job F. M.; de Boer, Michiel R.; Kocks, Janwillem W. H.; Berger, Marjolein Y.; van der Molen, Thys
Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a prevalent lung disease. It is assumed that severe patients will receive better treatment in specialised care centres but the prevalence of severe COPD in primary care is high. Integrated primary care services combine input from several sources and advice from pulmonologists to provide general practitioners with support needed to improve diagnosis and treatment of patients with COPD. Objectives: To evaluate patient-reported outcomes and costs of managing patients classified as GOLD D in an integrated primary care service over 12 months. Methods: Patients were included in this 1-year prospective cohort study if they met the 2014 GOLD D criteria, were aged ≥ 40 years and gave written informed consent for this study. Recruitment took place through the patients' general practitioners. The primary outcome was health status, assessed with the Clinical COPD Questionnaire (CCQ) and COPD Assessment Test (CAT). Secondary outcomes included self-reported exacerbations, quality-adjusted life years and health(care)-related costs. Results: Forty-nine patients were included. At baseline, the mean CAT score was 15.9 and the median CCQ score was 1.7. After 12 months, scores had improved by 2.3 (95% confidence interval, 0.8–3.7) and 0.4 (95% confidence interval, 0.2–0.7), respectively. Percentage of patients with ≥2 exacerbations in the past 12 months also decreased from baseline (77.6%) to 12 months (16.7%). Changes in mean quarterly costs were small. Conclusion: An integrated service for COPD based in primary care may improve the health status of patients with a large burden of disease while not increasing health care costs.